Tauroursodeoxycholic acid (TUDCA) attenuates pressure overload-induced cardiac remodeling by reducing endoplasmic reticulum stress - Rani, Shilpa (PLoS One, 2017)
Pressure overload in the heart induces pathological hypertrophy and is associated with cardiac dysfunction. Apoptosis and fibrosis signaling initiated by the endoplasmic reticulum stress (ERS) is known to contribute to these maladaptive effects. The aim of this study was to investigate whether reduction of ERS by a known chemical chaperone, tauroursodeoxycholic acid (TUDCA) can attenuate pressure overload-induced cardiac remodeling in a mouse model of transverse aortic constriction (TAC). Oral administration of TUDCA at a dose of 300 mg/kg body weight (BW) in the TUDCA-TAC group reduced ERS markers (GRP78, p-PERK, and p-eIf2α), compared to the Vehicle (Veh)-TAC group. TUDCA administration, for 4 weeks after TAC significantly reduced cardiac hypertrophy as shown by the reduced heart weight (HW) to BW ratio, and expression of hypertrophic marker genes (ANF, BNP, and α-SKA). Masson's trichrome staining showed that myocardial fibrosis and collagen deposition were also significantly reduced in the TUDCA-TAC group. We also found that TUDCA significantly decreased expression of TGF-β signaling proteins and collagen isoforms. TUDCA administration also reduced cardiac apoptosis and the related proteins in the TUDCA-TAC group. Microarray analysis followed by gene ontology (GO) and pathway analysis demonstrated that extracellular matrix genes responsible for hypertrophy and fibrosis, and mitochondrial genes responsible for apoptosis and fatty acid metabolism were significantly altered in the Veh-TAC group, but the alterations were normalized in the TUDCA-TAC group, suggesting potential of TUDCA in treatment of heart diseases related to pressure-overload.